(untitled) (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Rabies, is widespread in arctic and red foxes in Northern and Western Alaska, but not endemic in Interior Alaska. Areas with endemic rabies overlap with the habitat of the Arctic fox while regions solely inhabited by the red fox are considered free of endemic rabies. It is therefore not known if red foxes serve as competent long-term reservoirs for rabies or support only spill over infections. Three strains of rabies virus are present in Alaska with distinct geographic distribution. Furthermore climate change is expected to alter the distribution of these two species in Alaska, expanding the range of the red fox into the historic habitat of the arctic fox. We assessed the population structure of the two major hosts in Alaska, red and arctic foxes in the context of rabies strain distribution in Alaska. In contrast to previous studies on population structure of Arctic foxes in North America, we found significant structure in the population of arctic foxes, which correlates with the phylo-geographic distribution of rabies strains in Alaska. Red foxes also showed evidence of only limited gene flow between regions of Alaska.